The Developing Character in the Two Novels of Nasim Hijazi: Muhammad Bin Qasim and Islam Aur Duota - Dr Shameem Majeed Khatak; Dr Yaqoob Khan Marwat (Hazara Islamicus, 2015)
Naseem Hijazi is a famous Urdu novelist in history. The main point of his novels is the renaissance of Islamic history. He wants to reawaken the Muslim minds and youth through his novels. The main features of Naseem Hijazi is Deterrence, courage and truth because he wants to see these features in today's Muslims. Two round characters in his novels taken in this article are from Muhammad Bin Qasim's Gango and Islam wa Dawa's Sikh Day. Who reached faith and Islam through thought provoking stages.